The antidepressant-like effect of Ocimum basilicum in an animal model of depression. (18th August 2017) - Ali, SS; Abd El Wahab, MG; Ayuob, NN; Suliaman, M
Abstract: We investigated the efficacy of Ocimum basilicum (OB) essential oils for treating depression related behavioral, biochemical and histopathological changes caused by exposure to chronic unpredictable mild stress (CUMS) in mice and to explore the mechanism underlying the pathology. Male albino mice were divided into four groups: controls; CUMS; CUMS plus fluoxetine, the antidepressant administered for pharmacological validation of OB; and CUMS plus OB. Behavioral tests included the forced swim test (FST), elevated plus-maze (EPM) and the open ﬁeld test (OFT); these tests were performed at the end of the experiment. We assessed serum corticosterone level, protein, gene and immunoexpression of brain-derived neurotropic factor (BDNF) and glucocorticoid receptors (GRs) as well as immunoexpression of glial fibrillary acidic protein (GFAP), Ki67, caspase-3 in the hippocampus. CUMS caused depression in the mice as evidenced by prolonged immobility in the FST, prolonged time spent in the open arms during the EPM test and reduction of open field activity in the OFT. OB ameliorated the CUMS induced depressive status. OB significantly reduced the corticosterone level and up-regulated protein and gene expressions of BDNF and GR. OB reduced CUMS induced hippocampal neuron atrophy and apoptosis, and increased the number of the astrocytes and new nerve cells. OB significantly increased GFAP-positive cells as well as BDNF and GR immunoexpression in the hippocampus.